Mild pituitary phenotype in 3- and 12-month-old Aip-deficient male mice. Issue 1 (October 2016) - Lecoq, Anne-Lise; Zizzari, Philippe; Hage, Mirella; Decourtye, Lyvianne; Adam, Clovis; Viengchareun, Say; Veldhuis, Johannes D; Geoffroy, Valérie; Lombès, Marc; Tolle, Virginie; Guillou, Anne; Karhu, Auli; et al.
Abstract : Germline mutations in the aryl hydrocarbon receptor-interacting protein ( AIP ) gene predispose humans to pituitary adenomas, particularly of the somatotroph lineage. Mice with global heterozygous inactivation of Aip ( Aip +/− ) also develop pituitary adenomas but differ from AIP -mutated patients by the high penetrance of pituitary disease. The endocrine phenotype of these mice is unknown. The aim of this study was to determine the endocrine phenotype of Aip +/− mice by assessing the somatic growth, ultradian pattern of GH secretion and IGF1 concentrations of longitudinally followed male mice at 3 and 12 months of age. As the early stages of pituitary tumorigenesis are controversial, we also studied the pituitary histology and somatotroph cell proliferation in these mice. Aip +/− mice did not develop gigantism but exhibited a leaner phenotype than wild-type mice. Analysis of GH pulsatility by deconvolution in 12-month-old Aip +/− mice showed a mild increase in total GH secretion, a conserved GH pulsatility pattern, but a normal IGF1 concentration. No pituitary adenomas were detected up to 12 months of age. An increased ex vivo response to GHRH of pituitary explants from 3-month-old Aip +/− mice, together with areas of enlarged acini identified on reticulin staining in the pituitary of some Aip +/− mice, was suggestive of somatotroph hyperplasia. Global heterozygous Aip deficiency in mice is accompanied by subtle increase in GH secretion, which does not result in gigantism. The absence of pituitary adenomas in 12-month-old Aip +/− mice in our experimental conditions demonstrates the important phenotypic variability of this congenic mouse model.